2012
DOI: 10.1042/bj20112071
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure and functional characterization of a glucosamine-6-phosphate N-acetyltransferase from Arabidopsis thaliana

Abstract: GlcNAc (N-acetylglucosamine) is an essential part of the glycan chain in N-linked glycoproteins. It is a building block for polysaccharides such as chitin, and several glucosaminoglycans and proteins can be O-GlcNAcylated. The deacetylated form, glucosamine, is an integral part of GPI (glycosylphosphatidylinositol) anchors. Both are incorporated into polymers by glycosyltransferases that utilize UDP-GlcNAc. This UDP-sugar is synthesized in a short pathway comprising four steps starting from fructose 6-phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…T-DNA insertions in the exon of AtGFAT1 had a lethal effect (Table 1; Fig. 2A), which is consistent with previous reports showing the lethal phenotype of Arabidopsis mutants lacking glucosamine-6-phosphate N -acetyltransferase (GNA) and N -acetylglucosamine-1-P uridylyltransferase (GlcNAc1pUT) activity catalysing the second and last step of HBP, respectively (Riegler et al , 2012; Chen et al , 2014). However, T-DNA insertion in OsGNA1 of rice caused a defect in root elongation, but not a lethal phenotype (Jiang et al , 2005).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…T-DNA insertions in the exon of AtGFAT1 had a lethal effect (Table 1; Fig. 2A), which is consistent with previous reports showing the lethal phenotype of Arabidopsis mutants lacking glucosamine-6-phosphate N -acetyltransferase (GNA) and N -acetylglucosamine-1-P uridylyltransferase (GlcNAc1pUT) activity catalysing the second and last step of HBP, respectively (Riegler et al , 2012; Chen et al , 2014). However, T-DNA insertion in OsGNA1 of rice caused a defect in root elongation, but not a lethal phenotype (Jiang et al , 2005).…”
Section: Discussionsupporting
confidence: 91%
“…Recent work on genes encoding enzymes for the second and last steps of the HBP in plants have shown that the HBP is indispensable for plant growth and development, as in animals. For example, single base and knockout mutations in the GNA gene in Arabidopsis, encoding GlcN-6-P N -acetyltransferase, resulted in growth retardation and a lethal phenotype, respectively (Nozaki et al ., 2012; Riegler et al , 2012). The T-DNA insertion in GNA in rice reduced the wild-type UDP-GlcNAc content by about 90%, giving rise to abnormal root morphology (Jiang et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The pathway of de novo UDP‐GlcNAc synthesis originates from Fru‐6P, a glycolytic intermediate. l ‐Glutamine d ‐fructose‐6‐phosphate amidotransferase (GFAT), GNA1, and N ‐acetylglucosamine‐1‐phosphate uridylyltransferase (GlcNAc1pUT) are involved in this pathway[18–20]. GNK phosphorylates GlcNAc and produces GlcNAc‐6P, an intermediate of the de novo pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, the acceptor substrate in the reaction catalyzed by ScGNA1 (GlcN6P) has a much lower p K a (7.75) than that of other GNAT acceptor substrates and is likely to bind to the enzyme in a deprotonated form, eliminating the need for a general base [ 99 ]. The structures of the ScGNA1 homologs from Homo sapiens [ 100 , 101 ], Aspergillus fumigatus [ 100 ], Arabidopsis thaliana [ 102 ] and C. elegans [ 103 ] were also reported. The main-chain oxygen of E156 of human GNA1 (hGNA1) forms a hydrogen bond with the GlcN6P’s amino group and thus increases its nucleophilic nature.…”
Section: Overall Architecture Of General Control Non-repressible 5mentioning
confidence: 99%